2020
DOI: 10.1111/ddg.14048
|View full text |Cite
|
Sign up to set email alerts
|

S3 guideline for actinic keratosis and cutaneous squamous cell carcinoma – short version, part 1: diagnosis, interventions for actinic keratoses, care structures and quality‐of‐care indicators

Abstract: Summary Actinic keratoses (AK) are common lesions in light‐skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence‐based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was developed using the highest level of methodology (S3) according to regulations issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
141
0
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(177 citation statements)
references
References 16 publications
1
141
0
35
Order By: Relevance
“…This could be possibly explained by the fact that patients with statutory health insurance suspect that therapy in line with the guidelines is also fully reimbursed and that this does not result in any financial losses for them. A concrete counterexample is conventional PDT, which is uniformly recommended in current treatment guidelines [8,9] but has not yet been reimbursed by the statutory health insurance funds in Germany.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be possibly explained by the fact that patients with statutory health insurance suspect that therapy in line with the guidelines is also fully reimbursed and that this does not result in any financial losses for them. A concrete counterexample is conventional PDT, which is uniformly recommended in current treatment guidelines [8,9] but has not yet been reimbursed by the statutory health insurance funds in Germany.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple lesions, marked basal proliferation in histology, and additional signs of chronic UV damage on the adjacent skin increases the risk for progression considerably, and spontaneous regression is less likely to occur [5][6][7]. As it is clinically not possible to exactly predict which AK will become invasive cSCC, international treatment guidelines recommend early and consequent treatment [8,9]. Today, numerous interventions with varying efficacy and safety profiles are licensed for the management of AK.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the efficacy outcomes of interest were inconsistently reported. Results for lesion clearance were only available for ALA-PDT, demonstrating clearance of nearly 75% of all lesions, which is somewhat lower compared to previous pivotal trials [ 4 ]. Instead, the outcome participant complete clearance was reported in most of the included studies and revealed varying rates for the different interventions.…”
Section: Discussionmentioning
confidence: 97%
“…Further risk factors for the development of AK, besides advanced age, include male gender and fair skin type. Despite recent advancements in the prognostic classification of AK, pertinent guidelines recommend early and consequent treatment of AK, because it is currently not possible clinically or histologically to exactly delineate whether and which lesions will transform into cSCC [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, if multiple lesions or clinical signs of field cancerization are present, the progression rates increase markedly, and spontaneous regression is less likely to occur. International guidelines recommend early and consequent treatment of AK as it is clinically and histologically difficult to predict if and which lesions will progress into cSCC 4,5 . The concept of field cancerization has initiated a paradigm shift in AK therapy from lesion‐directed to field‐directed therapies.…”
Section: Introductionmentioning
confidence: 99%